Report of the twenty-fourth annual Trades union congress : held in the Town hall, Newcastle-upon-Tyne, on september 7, 8, 9, 10, 11 & 12, 1891 - Trades union congress (24 ; 1891 ; Newcastle-upon-Tyne)
Published by the authority of the Congress and the Parliamentary committee